Application of Miles and Snow’s as well as Kirton’s models in small- and medium-size enterprises: an exploratory study - de Vasconcelos, Ana Cecília Feitosa; Guedes, Isabela Assis; Cândido, Gesinaldo Ataíde (Revista Gestão da Produção Operações e Sistemas, 2007)
This paper aims at identifying the competitive strategies adopted by the footwear sector businessmen in the city of Campina Grande, state of Pernambuco, Brazil, as well as their possible association with their own cognitive styles xx. For this reason, the methods of direct in-company interviews and non-participative observation were applied. As a methodological tool for identifying the competitive strategies, the model xx proposed by Miles and Snow (1978) was used, and, for identifying xx the cognitive styles, xx the theory Kirton’s adaptation-innovation theory (1976) was used. It analyzes the influence of the xx leader’s creativity style on the enterprises’ strategic behavior xx. The results obtained by the survey point out to the prevalence of the xx defensive strategy by the footwear enterprises. With regard to the cognitive style adopted by the leaders of the surveyed enterprises, it was verified a concentration of managers presenting an adaptative cognitive style. Keywords: Footwear sector; Competitive strategy; Adaptation-innovation theory.